2009
DOI: 10.1590/s0100-879x2009000600005
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the hormone and lipid profile of obese adolescent Saudi females with acne vulgaris

Abstract: Acne vulgaris is a multifactorial disease affecting a majority of the adolescent population. The objective of this study was to test for a correlation between fasting serum lipid profiles and levels of testosterone, insulin, leptin, and interleukin 1-β (IL-1β) and the incidence of severe acne vulgaris in obese adolescent females. Four groups of adolescent females were studied: obese with acne, obese without acne, non-obese with acne, and non-obese without acne. Obese females with acne, compared to obese female… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
48
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(59 citation statements)
references
References 27 publications
7
48
0
4
Order By: Relevance
“…Here, it is speculated that high glycemic loads in Western diet could lead to increased androgens, increased insulin-like growth-factor 1, and altered retinoid signaling [44, 45]. In this context, such variables may also influence the skin microbiome.…”
Section: The Skin Microbiome In Human Diseasementioning
confidence: 99%
“…Here, it is speculated that high glycemic loads in Western diet could lead to increased androgens, increased insulin-like growth-factor 1, and altered retinoid signaling [44, 45]. In this context, such variables may also influence the skin microbiome.…”
Section: The Skin Microbiome In Human Diseasementioning
confidence: 99%
“…Abulnaj's studies of 2009 [67] demonstrated the significantly higher level of IL-1 beta in patients with acne. Similar results were obtained in a group of obese women and women without acne.…”
Section: Hormonal Disordersmentioning
confidence: 99%
“…Salah satu tanda kematuran pubertas adalah munculnya AV akibat peningkatan sebum dan sekresi hormon androgen (Herane dan Ando, 2003).Hormon androgen yang meningkat pada masa remaja dapat menyebabkan siklus menstruasi yang tidak teratur (Abulnaja, 2009).Ketidakteraturan siklus menstruasi juga disebabkan oleh ketidakseimbangan hormon estrogen dan progesteron (Qomaruddin, 2005). Hormon estrogen dan progesteron merupakan pemacu terjadinya AV sebelum menstruasi.…”
Section: Hubungan Antara Kelainan Siklus Menstruasi Dengan Kejadian Aunclassified